Biomechanical analysis of dragon boat paddling: A comparison of elite and sub-elite paddlers - Ho, S. R.; Smith, R.; O'Meara, D. (Journal of Sports Sciences, 2009)
In this study, video and force analysis techniques were used to distinguish between dragon boat paddlers of different ability. Six elite paddlers (three males, three females) and six sub-elite paddlers (two males, four females) were compared during high-intensity paddling (80-90 strokes · min-1). Video filming was conducted for two-dimensional kinematic analysis and an instrumented paddle was used to collect force data. Paddling efficiency, paddle force characteristics, and paddler kinematic variables were measured. Elite paddlers achieved higher paddling efficiency than sub-elite paddlers (elite: 76 ± 4%; sub-elite: 67 ± 10%; P = 0.080). Elite paddlers also showed higher peak force (elite: 16.3 ± 4.8 N · kg-2/3; sub-elite: 11.4 ± 2.6 N· kg-2/3; P = 0.052), average force (elite: 7.9 ± 2.8 N · kg-2/3; sub-elite: 5.5 ± 1.4 N · kg-2/3; P = 0.084), and impulse (elite: 3.0 ± 0.9 (N · s) · kg-2/3; sub-elite: 1.9 ± 0.4 (N · s) · kg-2/3; P = 0.026) than sub-elite paddlers, but these three results should be viewed with caution due to the small sample size and the unequal number of males and females in the two groups. Superior technique and greater strength enable the elite paddlers to achieve higher paddling efficiency. Paddlers use different joint movement patterns to develop propulsion, which are reflected in variations in the force-time curve.